Antarctic seismicity and neotectonics - Anya Reading (2002)
A map of Antarctic intraplate earthquakes, 1900-99, is presented including records from the Global Seismic Network and recordings made at Antarctic seismic observatories and temporary stations. The results show a low but significant level of seismicity through the Transantarctic Mountains and across George V Land to Adelie Land. They also suggest some seismic deformation is taking place in the Antarctic Peninsula, Weddell Sea, East Antarctic coast, and Ross Sea. No globally recorded events have occurred in Marie Byrd Land to date. Local recordings across the continent show that a denser distribution of recording stations is needed before drawing conclusions from areas of apparent Antarctic aseismicity. This review is one of the first contributions to the SCAR-approved ANTEC initiative, which aims to co-ordinate work on neotectonic deformation across the continent.